Cognitive Abilities and Earnings – First Evidence for Germany - Silke Anger; Guido Heineck (Applied Economics Letters, 2010)
We provide first evidence on the relationship between cognitive abilities and earnings in Germany using data from the German Socio-Economic Panel (SOEP) Study. The estimates suggest that mechanics abilities are positively related to wages of West German workers, even when educational attainment is controlled for. Pragmatics of cognition are not related to earnings. In line with studies for other countries, we find that ability and education are inseparable determinants of earnings.
Additional information: This is an author's accepted manuscript of an article published in Applied Economics Letters 17 (2010), 7, pp 699-702, available online at http://www.tandfonline.com/10.1080/13504850802297855
Keywords: J24; J31; I21; 330; Cognitive abilities; earnings regressions; returns to education; ability bias; Bildungsniveau; Lohndifferenzierung; Deutschland